Biomechanical analysis of different implant-abutments interfaces in different bone types: An in silico analysis - Pellizzer, Eduardo P. [UNESP]; Lemos, Cleidiel A.A. [UNESP]; Almeida, Daniel A.F.; de Souza Batista, Victor E. [UNESP]; Santiago Júnior, Joel F.; Verri, Fellippo R. [UNESP] (Elsevier, 2018)
The purpose of this study was to analyze the stress distribution of bone tissue around implants with different implant-abutment interfaces: platform switching (PSW); external hexagon (EH) and Morse taper (MT) with different diameters (regular: Ø 4 mm and wide: Ø 5 mm), bone types (I–IV) and subjected to axial and oblique load conditions using three-dimensional finite element analysis (3D-FEA). Sixteen 3D models of various configurations were simulated using InVesalius, Rhinoceros 3D 4.0, and SolidWorks 2011 software, and processed using Femap 11.2 and NeiNastran 11.0 programs. Axial and oblique forces of 200 N and 100 N, respectively, applied at the occlusal surface of prostheses. Maximum principal stress values were obtained from the peri-implant cortical bone of each model. Statistical analyses were performed using ANOVA and Tukey's test for maximum principal stress values. Oblique loading showed higher tensile stress than axial loading (P < 0.001). Wide-diameter implants showed lower stress concentration rather than regular-diameter implants, regardless of both connection and bone type (P < 0.001). Under axial loading, wide-diameter EH implants with regular platforms showed more favorable stress distribution than PSW implants for axial loading (P < 0.001); however, under oblique loading, PSW implants exhibited lower stress concentrations (P < 0.001). Regular-diameter MT implants showed lower stress than EH implants (P < 0.001). Bone type IV showed higher stress in the cortical region than bone types I and II (P < 0.001), but no significant difference when compared with bone type III (P > 0.05). The conclusion drawn from this in silico is that MT implants should be considered for use in situations that preclude the placement of wide-diameter implants, particularly where bone types III and IV are concerned.
Keywords: Bone type; Diameter; Finite element; Implant-abutment interfaces